Building and enhancing new literacies across the curriculum - Sadorra, Bryan Eli B.; Fernando, Madeline T., Gaoat, Gina Sylvia (Mandaluyong City, 2024)
BUILDING AND ENHANCING NEW LITERACIES ACROSS THE NEW CURRICULUM is a resource instructional material that corresponds with the content of the PPST-based syllabus for the course as prescribed in the CMO 30-8. 2017. This resource material consists of five chapters composed of lessons. Each esson follows a distinct format represented by the acronym GEAR UP which means Prepare or equip oneself for something or to get ready. Thus, this material will uip the pre-service teachers with the fundamental concepts and principles in rriculum and curriculum development, to make them ready to become teachers o will be building and enhancing literacies.
Keywords: Literary education-Cuirriculum